The impact of a particular warm-up on the demonstration of a badminton player’s reactive agility in game scenarios - Ponimasov O.E. (Theory and Practice of Physical Culture, 2025)
Objective of the study was to experimental validation of the efficacy of specific warm-up drills in enhancing the player’s reactive agility in tactical badminton scenarios. Methods and structure of the study. The study included 25 experienced male badminton players aged 20,3±1,6 years. They underwent a modified agility test twice – once without and once after a specific dynamic warm-up. The study measured the time it took for the players to respond to a visual signal. Results and conclusions. Following a preliminary specialized warm-up, all participants demonstrated improved reaction times. The mobilization stimuli provided by a series of specialized warm-up exercises, specifically designed to prepare for reactive coordination tasks, enhance the speed of motor response and the successful execution of coordination skills in badminton players.